Tinjauan Yurisdiksi dan Kepercayaan Konsumen dalam Hubungan antara Developer, Debitur, dan Perlindungan Konsumen dalam Pengadaan - Aliyah Risky Ramadhani; Muhammad Ihsan Hanafi; Fanny Nazalia Triananda; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
This article discusses the relationship between developers, debtors, and consumers in the procurement of housing and pharmaceutical management, focusing on consumer trust and legal protection. The research identifies key factors influencing this relationship, including the unclear legal status of properties in the housing sector, issues with credit transactions, and consumer protection in the pharmaceutical industry. The findings reveal that uncertainty faced by consumers in the housing sector, such as delays in construction and properties not meeting promises, can decrease consumer trust in developers. In the pharmaceutical sector, strong consumer protection and strict oversight of drug distribution play a crucial role in enhancing consumer satisfaction and trust in pharmaceutical products. This article suggests the need for clear regulations, stricter oversight, and transparency in both sectors to protect consumer rights and ensure healthy relationships between service or product providers and consumers. The government is expected to strengthen supervision and law enforcement to improve consumer trust and the sustainability of businesses in both sectors.